Pemodelan Wireframe Sistem Manajemen Proyek Perangkat Lunak (Studi Kasus: PT. Arkatama Multisolusindo) - Muhammad Fathur Rahman; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
A project management system is a software that is used in helping project managers supervise the completion of projects, especially software, some obstacles cause the project to be unsuccessful including poor management factors, and lack of user involvement in providing feedback. PT. Arkatama is one of the companies that use the software. The author finds that there are problems faced by PT. Arkatama at the time of using the software one of the problems found was the limitation of features and users because the software used was paid and required adjustments in advance so that there was a possibility of obstruction of project completion, from the findings of the problem the company decided to build a project management system by adjusting to the needs of the company and making the system an internal office application The author assists in supporting the creation of the system by analyzing the needs to model the wireframe. The stages of this study are realising the need to find the root of the problem, identifying mapped problems, then modeling business processes using the Business Process Model and Notation (BPMN), especially in the process of changing needs and reporting progress, then analyzing the need to obtain software features and modeled with use case diagrams and explained with use case scenarios and producing 41 use cases, lastly continued until creating a wireframe from the use case scenario. Then an evaluation was carried out on the wireframe to get input from stakeholders as software users, the evaluation results were obtained with 3 inputs and 3 suggestions for improvements that focused on the appearance of the system, and the last stage of checking the needs that have been described the evaluation is carried out with traceability to produce functional needs that have been defined correctly and are by the wireframe.